Effects of Different Local Commercial Feeds on the Performance of Layer Chickens at Zacky Farm, Blitar - Bagaskara, Muhammad Zacky Putra; Samur, Salnan Irba Novaela; Rahmawati, Resti Yuliana (Universitas Veteran Bangun Nusantara, 2025)
This study assessed the Performance of layer chickens fed with different local commercial feeds at Zacky Farm. The research was conducted at Zacky Farm, Kanigoro District, Blitar Regency, from October 2024 to November 2024. An experimental research method was employed, with a Completely Randomized Design (CRD). Data analysis was performed using One-Way ANOVA, followed by Duncan's Multiple Range Test if significant differences were found. The study included four treatments: P1 (brand J commercial feed), P2 (brand D commercial feed), and P3 (brand S commercial feed). Each treatment had five replications, with five-layer chickens per replication, resulting in a total population of 75-layer chickens. The results showed significant differences (P<0.05) between treatments P1, P2, and P3 for Feed Conversion Ratio (FCR) and Feed Intake (FI), which were 2.25; 3.08; 2.23 and 116.99 g/chicken/day; 155.014 g/chicken/day; 114.52 g/chicken/day, respectively. However, no significant differences were observed (P>0,05) for Hen Day Production (HDP), which were 92.40%, 92.40%, and 91.80%. This study concludes that the best Performance was observed in treatment P3, with an FCR of 2.23, an FI of 114.52 g/chicken/day, and an HDP of 91.80%.